HUBUNGAN STATUS FUNGSIONAL DAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI PASIEN PENYAKIT DALAM DI RUMAH SAKIT DR. CIPTO MANGUNKUSUMO JAKARTA - Befi - Sundari; Angga Rizqiawan; Wita Rizki Amelia; Astrine Permata Leoni; Ahmad Syauqy; Purwita Wijaya Laksmi; Ari Wijayanti; Lora Sri Nofi (PERSATUAN AHLI GIZI INDONESIA, 2023)
Malnutrition is a major problem among hospitalized patients. Nutritional problems can be influenced by an imbalance between the intake of macronutrients consumed, and a decrease in functional status among hospitalized patients. This study was conducted to analyze the relationship between functional status and food intake of macronutrients with the nutritional status of internal disease patients. This study used an observational design, with a cross-sectional approach. The sampling technique used was Consecutive Sampling with the number of respondents being 74 internal disease patients who were hospitalized at the RSCM. Functional status data were collected using the Barthel Index and macronutrient intake by interview using the Semi-Quantitative Food Frequency Questionnaire, and nutritional status using weight and height measurements was calculated using the BMI formula. The statistical analysis used is the Chi-Square test. There are 45.9 percent of respondents have poor nutritional status. The bivariate results showed that there was no significant relationship between functional status (p=0.950) and nutritional status and there was a significant relationship between energy intake (p=0.000), protein (p=0.000), fat (p=0.001), carbohydrates (p=0.001), with the nutritional status of internal disease patients. It can be concluded that there is a relationship between the intake of macronutrients, namely energy, carbohydrates, protein, fat, and the nutritional status of internal medicine patients at RSCM.Keywords: functional status, macronutrient intake, nutritional status ABSTRAK Malnutrisi merupakan masalah utama yang sering terjadi pada pasien di rumah sakit. Masalah gizi yang terjadi dapat dipengaruhi oleh ketidakseimbangan antara asupan zat gizi makro yang dikonsumsi, dan terjadi penurunan status fungsional pada pasien rawat inap. Penelitian ini dilakukan untuk menganalisis hubungan antara status fungsional dan asupan zat gizi makro dengan status gizi pasien penyakit dalam. Penelitian ini mengunakan desain observasional, dengan pendekatan cross-sectional. Teknik pengambilan sampel menggunakan Consecutive Sampling dengan jumlah responden 74 pasien penyakit dalam yang dirawat inap di RSCM. Pengumpulan data status fungsional menggunakan Barthel Index dan asupan zat gizi makro dengan wawancara menggunakan Semi-Quantitative Food Frequency Questionnaire, dan status gizi menggunakan pengukuran berat badan dan tinggi badan dihitung dengan rumus IMT. Analisis statistik yang digunakan adalah uji Chi-Square. Terdapat 45,9 persen responden memiliki status gizi kurang. Dari hasil bivariat menunjukkan tidak terdapat hubungan signifikan antara status fungsional (p=0,950) dengan status gizi dan terdapat hubungan yang signifikan antara asupan energi (p=0,000), protein (p=0,000), lemak (p=0,001), karbohidrat (p=0,001), dengan status gizi pasien penyakit dalam. Dapat disimpulkan bahwa adanya hubungan antara asupan zat gizi makro yaitu energi, karbohidrat, protein, lemak dengan status gizi pasien penyakit dalam di RSCM.Kata kunci: status fungsional, asupan zat gizi makro, status gizi